The THE EFFECT OF RELIGIOSITY ON THE PERFORMANCE OF ISLAMIC BANKING: A SYSTEMATIC LITERATURE REVIEW - Jon Kenedi; Syamsul Amar; Rosyeni Rasyid (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
This article aims to identify and analyze some of the main references regarding the relationship between religiosity and Islamic banking performance. The research method used is a systematic literature review using the Science Direct database from Elsevier. From several stages of systematic literature review, found 127 main references from journals ranked Q1 and Q2 from Scopus. This study finds that the journal that has the most influence on research on religiosity and Islamic banking performance is the International Journal of Information Management. In addition, this study also found that only one article actually analyzed the impact of religion (religiosity) on the performance of Islamic banks, so there is an opportunity to conduct research on the topic of religiosity and Islamic banking performance in the future with different regional contexts and variable relationships.